Analisis Komunikasi Bisnis Islam dalam Strategi Pemasaran UMKM Fesyen Muslim As-Shofa - Muhammad Nurcholish Arasyid; Wildan Munawar; Muhammad Amin (FEBI UIN Sunan Kalijaga, 2024)
The purpose of this research is to find out the marketing strategies implemented by As-Shofa business actors and also to find out whether the strategies implemented by As-Shofa business actors have implemented the principles of Islamic Business Communication. The approach taken is to use descriptive qualitative data analysis techniques used, namely the Miles and Huberman technique and also the checklist matrix, data collection through interviews and documentation. Based on the research results, As-Shofa MSME business communication has implemented Islamic business communication, but not all principles have been applied to business communication. In each communication variable there are principles of Islamic business communication contained, among others, (1) The communicator is a person who has credibility so that the principle of consideration is applied to, (2) Messages and information given to the communicant to the point apply the principles of clarity and concreteness , (3) The communication of each strategy is adjusted to the purpose of the communication, the communicants are people who need information on UMKM As-Shofa products so that this variable applies the principle of Conciseness, (4) The context of communication carried out in each strategy is adjusted to the purpose of this is to apply the principle of concreteness, (5) Most of the communication channels used in each strategy are direct verbal communication (face to face). In direct communication, communication is quite effective, because there is direct interaction between the communicator and the communicant. When there is an error message, direct communication can be straightened out because of interactive communication. In this communication channel, the principle of Consideration is applied.